ከውሃው በላኝ ወደ ውሃ አበላኝ /Kä Wuhaw Bälañ Wädä Wuha Abälañ (From WaterLlogged Me to Water Nourished Me*): A Historical Analysis of Rice Production on Enhancing Livelihood in Fogera Woreda, 1970s to 2017 - Getinet Merid Ekimie (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2022)
This article explores the introduction of rice production in Fogera woreda mainly associated with the government initiative of ensuring food security for households at the beginning of the 1970s. The woreda has well-suited agro-ecology for the production of rice. Hence, this study attempts to investigate examine and assess the contribution of rice production to the income and food security of rural households in Fogera Woreda, South Gondar Zone. To achieve the objective, the researcher used a qualitative research method. The data was collected from primary and secondary sources. Primary sources were collected through key informant interviews and archival sources while secondary sources were obtained from relevant literature such as books, journals, articles, study reports, and theses. The study result shows that farmers in Fogera plain have benefited from rice production. The implica- tion of rice production on the socio-economic life of society was seen since its introduction. Hence, rice production in Fogera is one of the most essential achievements of the society which changes the life of peasants incredibly well.